2016
DOI: 10.1016/j.neuron.2016.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Long-Distance Descending Spinal Neurons Ensure Quadrupedal Locomotor Stability

Abstract: Locomotion is an essential animal behavior used for translocation. The spinal cord acts as key executing center, but how it coordinates many body parts located across distance remains poorly understood. Here we employed mouse genetic and viral approaches to reveal organizational principles of long-projecting spinal circuits and their role in quadrupedal locomotion. Using neurotransmitter identity, developmental origin, and projection patterns as criteria, we uncover that spinal segments controlling forelimbs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
161
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(171 citation statements)
references
References 63 publications
(87 reference statements)
10
161
0
Order By: Relevance
“…One role of ipsilateral inhibition is to mediate flexor-extensor alternations via Ia reciprocal inhibition from V2b and V1 populations [18, 19]. Ipsilaterally descending propriospinal neurons may also stabilize left-right alternation, although specific ablation of inhibitory ipsilaterally descending neurons has not been tested [8, 59]. Our work establishes that selective suppression of V2b activity increases tail beat frequency (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…One role of ipsilateral inhibition is to mediate flexor-extensor alternations via Ia reciprocal inhibition from V2b and V1 populations [18, 19]. Ipsilaterally descending propriospinal neurons may also stabilize left-right alternation, although specific ablation of inhibitory ipsilaterally descending neurons has not been tested [8, 59]. Our work establishes that selective suppression of V2b activity increases tail beat frequency (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Reticulospinal systems control adult body and eye movements (Sparks, 2002;Dubuc et al 2008;Jordan et al 2008;Arber, 2012;Ruder et al 2016) but it is the mammal cortical decision circuits, which act as higher level control systems, that have been studied in such detail (Hanes & Schall, 1996;Schall, 2003;Smith & Ratcliff, 2004). Our findings suggest that at early stages of development in tadpoles and fish (Kimura et al 2013) decisions are made in reticulospinal neurons in the brainstem.…”
Section: How Do Our Findings In the Tadpole Relate To Models Of Decismentioning
confidence: 76%
“…; Arber, ; Ruder et al . ) but it is the mammal cortical decision circuits, which act as higher level control systems, that have been studied in such detail (Hanes & Schall, ; Schall, ; Smith & Ratcliff, ). Our findings suggest that at early stages of development in tadpoles and fish (Kimura et al .…”
Section: Discussionmentioning
confidence: 99%
“…While neuronal mechanisms involved in left-right coordination of hindlimbs are mostly driven by segmental spinal neurons and fairly well understood (Kiehn, 2016), much less is known about circuit mechanisms for foreand hindlimb coordination. A recent study demonstrated that long projection neurons interconnecting the cervical and lumbar spinal cord are important in coordinating fore-and hindlimb patterns during high-speed locomotion as well as for maintenance of postural stability ( Figure 2C) (Ruder et al, 2016). The characterized long projection neurons are composed of a major excitatory and a minor inhibitory population derived from distinct developmental origin, each establishing specific projection patterns ( Figure 2C).…”
Section: Neuronmentioning
confidence: 96%